فعالية برنامج للعلاج الوظيفي في خفض بعض الاضطرابات الحسية لدى أطفال ذوي اضطراب التوحد - عزازي، أحمد محمد عاطف (رابطة التربويين العرب, 2017)
هدف البحث إلى الكشف عن فعالية برنامج للعلاج الوظيفي في خفض بعض الاضطرابات الحسية لدى الأطفال ذوي اضطراب التوحد، ومدى استمرارية فعالية البرنامج بعد فترة المتابعة (شهر بعد انتهاء تطبيق البرنامج)، وقد تكونت عينة البحث من (10) أطفال ذوي اضطراب التوحد، تتراوح أعمارهم بين (٦ -٩) سنة، بمتوسط عمري (7.7)، وانحراف معياري (0.909)، وهم من فئة متوسطي اضطراب التوحد، تتراوح نسبة ذكائهم (٥٥ -٧٠) درجة، بمتوسط ذكاء (65.6)، وانحراف معياري (6.31)، وتم استخدام اختبار ستانفورد بينيه للذكاء الصورة الخامسة تعريب وتقنين صفوت فرج (٢٠١١)، ومقياس الطفل التوحدي إعداد عادل عبد الله (٢٠٠٢)، ومقياس الاضطرابات الحسية للأطفال ذوي اضطراب التوحد إعداد الباحث، وبرنامج مقترح للعلاج الوظيفي إعداد الباحث، وبعد معالجة البيانات إحصائيا أشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي رتب درجات أفراد المجموعة التجريبية على مقياس الاضطرابات الحسية في كل من القياسين القبلي والبعدي. ووجود فروق ذات دلالة إحصائية عند مستوى (٠.٠١) بين متوسطي رتب درجات أفراد المجموعتين التجريبية والضابطة على مقياس الاضطرابات الحسية في القياس البعدي. كما أشارت النتائج إلى عدم وجود فروق ذات دلالة إحصائية بين متوسطي رتب درجات أفراد المجموعة التجريبية على مقياس الاضطرابات الحسية في كل من القياسين البعدي والتتبعي.
The study aimed to reveal the effectiveness of Occupational Therapy program to reduce some Sensory disorder in children with autism, and knowing the continuity of the program effect after the follow-up period. The study sample consisted of (10) children with autism aged (6-9) years, with an average age of (7.7), SD (0.909) with autism spectrum disorder, with IQ (55- 70), with an average intelligence of (65.6), SD (6.31), Stanford-Binet test for intelligence, the fifth image, standardized by Safwat Faraj (2011), autistic child scale prepared by Adel Abdullah (2002), sensory disorders for children with autism spectrum disorder scale and a proposed program of occupational therapy (by the researcher). After manipulating data statistically, the research findings indicated that there were statistically significant differences at (0.05) between the mean scores of experimental groups on sensory disorders scale in pre- and post-assessments. There were statistically significant differences (0.01) between the mean scores of experimental and control groups on sensory disorders scale in post-assessments. The results also indicated that there were no statistically significant differences between the mean scores of the experimental group on sensory disorders scale, in post- and follow-up assessments.
Keywords: علم النفس العلاجي -- اضطراب طيف التوحد -- العلاجي الوظيفي -- أطفال طيف التوحد